2016
DOI: 10.11604/pamj.2016.24.270.8429
|View full text |Cite
|
Sign up to set email alerts
|

African civil society initiatives to drive a biobanking, biosecurity and infrastructure development agenda in the wake of the West African Ebola outbreak

Abstract: This paper describes the formation of a civil society consortium, spurred to action by frustration over the Ebola crises, to facilitate the development of infrastructure and frameworks including policy development to support a harmonized, African approach to health crises on the continent. The Global Emerging Pathogens Treatment Consortium, or GET, is an important example of how African academics, scientists, clinicians and civil society have come together to initiate policy research, multilevel advocacy and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…56 Unfortunately, there is little investment in biorepository and biobank infrastructure for ongoing and future research in SSA. 57 The limited ability to store biological samples and data during the COVID-19 pandemic will significantly limit the conduct of future research in the region. COVID-19 related research should be approved by the appropriate ethics committees, with considerations for research protocols to be fast-tracked.…”
Section: Rapid Data Sharingmentioning
confidence: 99%
“…56 Unfortunately, there is little investment in biorepository and biobank infrastructure for ongoing and future research in SSA. 57 The limited ability to store biological samples and data during the COVID-19 pandemic will significantly limit the conduct of future research in the region. COVID-19 related research should be approved by the appropriate ethics committees, with considerations for research protocols to be fast-tracked.…”
Section: Rapid Data Sharingmentioning
confidence: 99%
“…By rapidly amending existing protocols in collaboration with those Principal Investigators and through the volunteered time of Obstetrics and Neonatology clinicians, we were able to rapidly enroll and collect high quality, wide-ranging sample types from pregnant women and their newborns. Attempts to develop biobanks from other devastating pandemics, such as the Ebola crisis in West Africa [ 31 ], have also shown that identifying infrastructure gaps and points of cultural sensitivity are critical to achieving a successful biobank relevant to the population it serves. Data from our group and others have demonstrated that COVID-19 disease has disproportionately affected people of color and lower socioeconomic status [ 22 , 32 – 35 ], widening health disparities.…”
Section: Discussionmentioning
confidence: 99%
“…There has also been a lack of concerted effort to ensure that these leaders contribute to sustainable change-by addressing both challenges related to isolation and burnout, and lack of incentives and support for these workers to build skills and to share knowledge among their teams and within the organizations where they work. In parallel, as the problems faced by health systems around the world continue to become more numerous and complex (e.g., communicable and non-communicable diseases, climate change, rising inequities, and outbreaks, such as Ebola and COVID-19), many have raised the concern that current models for managing these challenges are too fragmented, inefficient, and untenable [18][19][20][21]. Against this backdrop, the audacious vision to support capacity strengthening through partnerships, networking, mentorship, and an explicit focus on leadership and management skills needed for the local context has gained traction among donors and host institutions.…”
Section: Contextual Factorsmentioning
confidence: 99%